Detrital zircon (U-Th)/He ages from Paleozoic strata of the Severnaya Zemlya Archipelago: Deciphering multiple episodes of Paleozoic tectonic evolution within the Russian High Arctic. (September 2018) - Ershova, Victoria; Anfinson, Owen; Prokopiev, Andrei; Khudoley, Andrei; Stockli, Daniel; Faleide, Jan Inge; Gaina, Carmen; Malyshev, Nikolay
Abstract: Combined (U-Th)/He and U-Pb detrital zircon geochronological data are reported from Ordovician to Devonian strata of the Severnaya Zemlya archipelago to address the paleogeography of the Kara Terrane in the Russian High Arctic. (U-Th)/He ages from all six samples analyzed were not reset after sediment deposition, indicating that detrital zircons carry information on the exhumation history in the source region of the clastic material. In Ordovician-Silurian strata, (U-Th)/He ages range from 583.8 ± 46.7 to 429.0 ± 34.3 Ma. These ages nicely coincide with significant regional exhumation during the Caledonian and Timanian orogenies. In addition, combined U-Pb and (U-Th)/He dating show that within the source region, zircons that were crystalized during the Timanian Orogeny (U-Pb ages 680–560 Ma) were likely exhumed during younger Caledonian events ((U-Th)/He ages of 455–495 Ma), suggesting potential overlap of these orogens within the source region. In Devonian strata, detrital zircon (U-Th)/He ages range from 517.2 ± 41.38 to 332.9 ± 26.6 Ma, with a peak age of ca. 375 Ma. This 375 Ma event may be correlated with either the Ellesmerian Orogeny or the terminal Solundian/Svalbardian stages of the Caledonian Orogeny.